How well do FIFA`s ratings predict World Cup success? - Stefani, R. (Significance, 2014)
The first match has yet to kickoff, but it`s not too early for the weeping and gnashing of teeth to begin. Fans of the 32 World Cup teams already worry that their group is too hard and their hated rival`s group is too easy, based on FIFA`s team ratings. Just how much of a bellwether have those ratings been? FIFA changed the original 1993 system in 1999 (for the worse as we shall see) and again in 2006 (for the better).